2018
DOI: 10.1002/rth2.12071
|View full text |Cite
|
Sign up to set email alerts
|

The impact of repeated freeze‐thaw cycles on antiphospholipid antibody titer

Abstract: Essentials Limited data are available of freeze‐thaw effect on anticardiolipin and anti‐beta2‐glycoprotein I antibodies.Patient samples with antibody titer over a broad range were analyzed in a standardized freezing‐thawing scheme.aCL and aβ2GPI IgG and IgM titers are stable over time and after repeated freeze‐thawing.Repeated use of samples facilitates routine work‐out and use of samples for scientific purposes. BackgroundPre‐analytical factors, like freeze‐thaw cycles (FTC), can potentially affect results a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
(14 reference statements)
1
6
0
Order By: Relevance
“…While we do not expect repeated freeze-thaw cycles in routine clinical diagnostic settings, serum specimens that have been frozen as a result of repeated serological testing for different diseases without aliquoting are expected to yield results similar to fresh sera. Our results are consistent with previous studies evaluating the stability of IgM and IgG after repeated freeze-thaw cycles via sensitive enzyme immunoassays [10,11] and adds to the body of evidence that the precipitating characteristics of antibodies (e.g. F c region [5]) against Aspergillus have not been functionally altered.…”
Section: Discussionsupporting
confidence: 91%
“…While we do not expect repeated freeze-thaw cycles in routine clinical diagnostic settings, serum specimens that have been frozen as a result of repeated serological testing for different diseases without aliquoting are expected to yield results similar to fresh sera. Our results are consistent with previous studies evaluating the stability of IgM and IgG after repeated freeze-thaw cycles via sensitive enzyme immunoassays [10,11] and adds to the body of evidence that the precipitating characteristics of antibodies (e.g. F c region [5]) against Aspergillus have not been functionally altered.…”
Section: Discussionsupporting
confidence: 91%
“…The authors studied PT, APTT, Fibrinogen, D‐Dimer, clot‐based FII/FV/FVII/FVIII/FIX/FXI/FXII, chromogenic FXIII, AT activity, PC activity, PS activity plasminogen, DRVVT and anti‐Xa (LMWH). Five freeze‐thaw cycles did not cause significant changes in anticardiolipin or anti β2 glycoprotein 1 antibody testing 82 . Taken together, these studies indicate that many coagulation tests can be safely performed after 2 cycles of freeze thaw when thawing is done in a water bath for 4‐5 minutes and freezing/refreezing is done at −70°C, provided the interval between thaw and refreeze takes account of sample stability (see Section 6 above).…”
Section: Secondary Aliquots—transport Storage and Processingmentioning
confidence: 72%
“…Five freeze-thaw cycles did not cause significant changes in anticardiolipin or anti β2 glycoprotein 1 antibody testing. 82 Taken together, these studies indicate that many coagulation tests can be safely performed after 2 cycles of freeze thaw when thawing is done in a water bath for…”
Section: S Econdary Aliquots -Tr Ans P Ort S Tor Ag E and Pro Ce Ss Ingmentioning
confidence: 80%
“…Therefore, it is recommended to store sera in aliquots to reduce sample exposure to multiple F/T cycles [6]. Although several studies have suggested that repeated F/T cycles have a minimal effect on antibody stability against specific pathogens [2,7,8], other researchers are questioning the reliability of the data generated from using such samples [9].…”
Section: Introductionmentioning
confidence: 99%